Adenosine Inhibits the Excitatory Synaptic Inputs to Basal Forebrain Cholinergic, GABAergic, and Parvalbumin Neurons in Mice - Yang, Chun; Franciosi, Serena; Brown, Ritchie E. (Frontiers in Neurology, 2013)
Coffee and tea contain the stimulants caffeine and theophylline. These compounds act as antagonists of adenosine receptors. Adenosine promotes sleep and its extracellular concentration rises in association with prolonged wakefulness, particularly in the basal forebrain (BF) region involved in activating the cerebral cortex. However, the effect of adenosine on identified BF neurons, especially non-cholinergic neurons, is incompletely understood. Here we used whole-cell patch-clamp recordings in mouse brain slices prepared from two validated transgenic mouse lines with fluorescent proteins expressed in GABAergic or parvalbumin (PV) neurons to determine the effect of adenosine. Whole-cell recordings were made BF cholinergic neurons and from BF GABAergic & PV neurons with the size (>20 µm) and intrinsic membrane properties (prominent H-currents) corresponding to cortically projecting neurons. A brief (2 min) bath application of adenosine (100 μM) decreased the frequency but not the amplitude of spontaneous excitatory postsynaptic currents in all groups of BF cholinergic, GABAergic and PV neurons we recorded. In addition, adenosine decreased the frequency of miniature EPSCs in BF cholinergic neurons. Adenosine had no effect on the frequency of spontaneous inhibitory postsynaptic currents in cholinergic neurons or GABAergic neurons with large H-currents but reduced them in a group of GABAergic neurons with smaller H-currents. All effects of adenosine were blocked by a selective, adenosine A1 receptor antagonist, cyclopentyltheophylline (CPT, 1 μM). Adenosine had no postsynaptic effects. Taken together, our work suggests that adenosine promotes sleep by an A1-receptor mediated inhibition of glutamatergic inputs to cortically-projecting cholinergic and GABA/PV neurons. Conversely, caffeine and theophylline promote attentive wakefulness by inhibiting these A1 receptors in BF thereby promoting the high-frequency oscillations in the cortex required for attention and cognition.